Nezara viridula (Hemiptera: Pentatomidae) transcriptomic analysis and neuropeptidomics - Lavore, Andrés (2018)
Stinkbugs (Hemiptera: Pentatomidae) are of major economic importance as pest of crops. Among the species composing the stinkbug complex, Nezara viridula is one of the most abundant in Brazil, Argentina and the Southern USA. However, this species has been poorly characterized at the genetic and physiological level. Here we sequenced and analyzed the complete transcriptome of N. viridula male and female adults. We identifed neuropeptide precursor genes and G-protein coupled receptors for neuropeptides in this transcriptome. Mature neuropeptides were identifed in N. viridula brain extracts by liquid chromatography-tandem mass spectrometry. We also analyzed the neuropeptide precursor complement in the genome sequence of Halyomorpha halys, another pentatomid of economic relevance. We compared the results in both pentatomids with the well-characterized neuropeptide repertoire from the kissing bug Rhodnius prolixus (Hemiptera: Reduviidae). We identifed both groupspecifc features (which could be related to the diferent feeding habits) and similarities that could be characteristic of Heteroptera. This work contributes to a deeper knowledge of the genetic information of these pests, with a focus on neuroendocrine system characterization.